Clinical and histopathological prognostic factors affecting the renal outcomes in childhood ANCA-associated vasculitis - ALPAY, HARİKA; GÖKCE, İBRAHİM (SPRINGER, 2019)
ObjectiveAntineutrophil cytoplasmic antibody (ANCA)-associated vasculitides (AAV) are very rare in childhood with an increased risk of morbidity and mortality. We aimed to evaluate renal prognostic factors in childhood AAV from the perspective of ANCA serotype, histopathological classification, and five-factor score (FFS).MethodsPediatric AAV patients from 11 referral centers in Turkey had been included to the study. The demographics, clinical findings, AAV subtypes, outcomes, and FFS were evaluated retrospectively. Kidney biopsies were classified histopathologically.ResultsTotally, 39 patients were enrolled in the study. Among all patients, 74.4% had renal involvement, 56.4% ear-throat-nose involvement, and 51.3% had musculoskeletal involvement. Proteinase 3 (PR3)-ANCA was positive in 48.7%, and myeloperoxidase (MPO)-ANCA was positive in 30.8%. 69.2% of patients had impaired renal function, and 28.2% had progressed to end-stage renal disease (ESRD) during the follow-up. At the time of diagnosis, FFS was 2 in 53.8%. The most common histopathologic classifications were as follows: crescentic type in 40.7% and sclerotic type in 25.9%. Gastrointestinal and renal involvement, MPO-ANCA positivity, serum creatinine levels, and impaired renal function during the follow-up were significantly higher in patients with FFS2, compared to patients with FFS <2. Patients with FFS2 had more common crescentic, mixed and sclerotic histopathologic findings in biopsies. By logistic regression analysis forward method, the strongest single-risk factor among all the parameters was the initial level of creatinine in patients with ESRD, compared to the other patients (p=0,007).ConclusionsEvaluation of the FFS, ANCA serology, and the creatinine levels may help to predict renal prognosis.
Keywords: Antineutrophil cytoplasmic antibody-associated vasculitides; Five-factor score; Renal involvement; ANCA; Histopathology; CHURG-STRAUSS-SYNDROME; WEGENER GRANULOMATOSIS; POLYARTERITIS-NODOSA; CLASSIFICATION; CRITERIA; GLOMERULONEPHRITIS; POLYANGIITIS; CHILDREN; FEATURES